RETURN OF COMPULSORY MILITARY SERVICE IN EUROPE: SOCIAL DETERMINISM AND PERSPECTIVES - Starčević, Srđan (The Policy of National Security, 2024)
In the period between 1995 and 2012, a number of European countries suspended mandatory military service upon which European national standing armies were based, from the 19th to the end of the 20th century. The Second Crimean crisis, which yielded the renewed perception of Russia as a threat to the West, caused a narrative shift regarding military organization in Europe placing public expression of concern for efficiency of its military and its deterrence capability on the public agenda.   The subject of this paper is the analysis of social facts that obstruct political decision-making on military conscription in European societies or hinder the process of reinstating mandatory military service in European countries. The aim is to point out the social determinisms that discourage the introduction of mandatory military service in Europe while favouring the professional military as the basic type of military organization of modern European societies with private military companies as its “subcontractors” and auxiliary forces. The hypothesis proven by the paper is that social changes that took place at the end of the 20th and the beginning of the 21st century shaped modern European societies using dominant social values in contrast to the social values traditionally implied by mandatory military service and conscription. Zygmunt Bauman's theory of fluid modernity was used for the purposes of the paper, supplemented with Giovanni Sartori's theoretical considerations on the rights-claiming society. Hypothetical-deductive and historical-comparative methods were used in the paper.The introduction explains the conditions under which mandatory military service was introduced in European countries as well as the criticism it faced previous to its suspension. The first chapter is devoted to the analysis of the reasons for reintroducing mandatory military service. In the second chapter, the social facts that resist the return of mandatory military service are analysed. These facts include: decline of power of nation states and redefinition of the concept of sovereignty during globalization, the rise of a type of society that can be called consumerist, atomized, and rights-claiming society, and the shaping of culture with a hedonistic cultural strategy. Social values of modern society are in contrast to social values on which conscription societies counted on: supremacy of the collective over the individual, disciplined repetition of routines, awareness of continuance of the nation as a higher form of shared existence for which a certain absence of comfort must be endured, along with the willingness to make personal sacrifices for the common good.Based on historical experience, the multipolar world will be a world of military competition and it is expected that many countries will attempt to reintroduce conscription. States which are able to convince their citizens that the danger to the country’s freedom is realistic, will introduce this obligation provided that it takes a looser form than the one that was in force in the last century. Those countries that have suspended the obligation to serve in the military and wish to restore it but fail to convince their citizens of the reality of the threat, will face clear discontent of their citizens.
Keywords: conscription; military service; nation-state; globalization; technologization; consumer society; professional armed forces